2013
DOI: 10.3390/life3030502
|View full text |Cite
|
Sign up to set email alerts
|

Natural Pyrrhotite as a Catalyst in Prebiotic Chemical Evolution

Abstract: The idea of an autotrophic organism as the first living being on Earth leads to the hypothesis of a protometabolic, complex chemical system. In one of the main hypotheses, the first metabolic systems emerged from the interaction between sulfide minerals and/or soluble iron-sulfide complexes and fluids rich in inorganic precursors, which are reduced and derived from crustal or mantle activity. Within this context, the possible catalytic role of pyrrhotite, one of the most abundant sulfide minerals, in biomimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…While XRD analyses did not identify Fe 1– x S produced during abiotic reduction of FeS 2 reduction by H 2 , it was still the favored secondary mineral to form on the surface of FeS 2 based on thermodynamic calculations and observations from studies conducted at higher temperature ( Truche et al, 2010 ). Thus, the solubility of Fe 1– x S was examined to identify its plausibility as a source of soluble Fe and S. Specimen Fe 1– x S obtained from Aymar quarry, Gualba mines, Gualba, Montseny, Barcelona Spain, which has previously been shown to be of high purity ( de Aldecoa et al, 2013 ), was used in experiments. XRD of the mineral indicated that the only FeS phase present was Fe 1– x S (∼80%) with the balance as quartz ( Supplementary Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…While XRD analyses did not identify Fe 1– x S produced during abiotic reduction of FeS 2 reduction by H 2 , it was still the favored secondary mineral to form on the surface of FeS 2 based on thermodynamic calculations and observations from studies conducted at higher temperature ( Truche et al, 2010 ). Thus, the solubility of Fe 1– x S was examined to identify its plausibility as a source of soluble Fe and S. Specimen Fe 1– x S obtained from Aymar quarry, Gualba mines, Gualba, Montseny, Barcelona Spain, which has previously been shown to be of high purity ( de Aldecoa et al, 2013 ), was used in experiments. XRD of the mineral indicated that the only FeS phase present was Fe 1– x S (∼80%) with the balance as quartz ( Supplementary Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the peaks remained in the same position. However, some of the peaks were intensified such as those at 2 θ =35.5° and 36.5° which corresponded to the pyrrhotite and pentlandite materials . Therefore, the potential cycling process was influencing the crystallinity of the material which subsequently resulted in a 3 fold improvement in the current density of the catalyst for the OER at 1.7 V (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical systems have been recently suggested as a relevant approach to study prebiotic chemistry related to hydrothermal vents scenario (de Aldecoa et al, 2013 ; Barge et al, 2014 , 2015 ; Herschy et al, 2014 ; Yamaguchi et al, 2014 ; Roldan et al, 2015 ). The focus of these studies is usually on abiotic CO 2 reduction and reduced iron sulfides and sometimes iron oxides (green rust) are considered as possible electrode candidates.…”
Section: Discussionmentioning
confidence: 99%